The optimal true ileal digestible threonine requirement for nursery pigs between 24 to 49 lb - James, B.W.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 22-d growth assay was conducted to determine the appropriate true ileal digestible threonine requirement to maximize growth performance of pigs between 24 and 49 lb. The 10 experimental treatments consisted of two basal diets (1.1% and 1.2% true ileal digestible lysine; 16.1% and 17.4% CP) with increasing levels of threonine (50, 55, 60, 65, 70% threonine:lysine). Pigs fed 1.2% true ileal digestible lysine had improved ADG and F/G compared to pigs fed 1.1% lysine, this suggest that the requirement was greater than 1.1% true ileal digestible lysine. There was a threonine × lysine interaction for feed efficiency. Pigs fed 1.1% true ileal digestible lysine had a greater response to increasing levels of threonine than pigs fed the diet containing 1.2% lysine. Increasing levels of threonine had no effect on ADG. Feed efficiency improved with increasing levels of true ileal digestible threonine:lysine and was maximized at 70% and 65% threonine:lysine for pigs fed 1.1% and 1.2% true ileal digestible lysine, respectively. However, the greatest improvements in feed efficiency were observed as the ratio increased to approximately 60%.
Keywords: Threonine; Growth Performance; Nursery Pigs; Swine